Simulation-Based Decision Support System for Energy Efficiency in Buildings Retrofitting - Neves-Silva, Rui (2022)
Funding Information: This research was developed under project EnPROVE (Energy Consumption Prediction with Building Usage Measurements for Software-Based Decision Support) funded by the European Union’s Seventh Framework Programme (Grant agreement ID: 248061). Partial support was also given by the Portuguese “Fundação para a Ciência e Tecnologia (FCT)” through the project UIDB/00066/2020 (Center of Technology and Systems, CTS). Publisher Copyright: © 2022 by the authors.